DECOMPOSITIONS OF COMPLETE GRAPHS INTO KAYAK PADDLES - Dalibor Froncek; Leah Tollefson (Journal of the Indonesian Mathematical Society, 2011)
A canoe paddle is a cycle attached to an end-vertex of a path. It was shown by Truszczynski that all canoe paddles are graceful and therefore decompose complete graphs. A kayak paddle is a pair of cycles joined by a path. We prove that the complete graph K2n+1 is decomposable into kayak paddles with n edges whenever at least one of its cycles is eve.DOI : http://dx.doi.org/10.22342/jims.0.0.17.39-44